Chemical Constituents from Termite‐associated Xylaria acuminatilongissima YMJ623. Issue 5 (6th May 2016) - Cho, Ting‐Yu; Wang, Guei‐Jane; Ju, Yu‐Ming; Chen, Mei‐Chuan; Lee, Tzong‐Huei
Abstract: Three previously unreported benzofurans, namely acumifurans A–C (1 –3 ), along with five known compounds, 2‐(isopropyl‐1′‐ol)‐2, 3‐dihydrobenzofuran‐5‐carbinol (4 ), fomannoxin alcohol (5 ), fomannoxin (6 ), acremine S (7 ) and cyclo (L ‐Pro‐L ‐Leu) (8 ), were isolated from the ethyl acetate extracts of the fermented broths of termite n est associated Xylaria acuminatilongissima YMJ623. Compound4, a synthe tic benzofuran analogue of1 –3, was isolated for the first time from natural resources. The str uctures of1 –8 were determined through spectroscopic data analyses. The absolute configurations of1 –4 were established based mainly on ROESY experiment and Mosher's reaction, and compared the optical rotation data with the literatures. The effects of these compounds on the inhibition of NO production in lipopolysaccharide (LPS)‐activated murine macrophage RAW264.7 cells were also evaluated. Of the compounds tested, 6 showed a mild NO production inhibitory activity without any cytotoxicity, and its mean maximum inhibition ( E max ) at 100 μM was 42.98±0.87 %. Abstract : Eight compounds including three new benzofurans1 –3 were isolated from the ethyl acetate extracts of the fermented broth of termite‐associated Xylaria acuminatilongissima YMJ623. The absolute configurations of1 –4 were established based on optical rotational data, ROESY experiments and Mosher's reaction. Benzofuran analogue6 showed mild NO production inhibitory activity on LPS‐induced RAW264.7 cells.